Effect of the Interaction of Veratrum Nigrum with Panax Ginseng on Estrogenic Activity In Vivo and In Vitro - Xu, Ying (Sci Rep, 2016)
Panax ginseng (GS) and Veratrum nigrum (VN) are representative of incompatible pairs in “eighteen antagonistic medicaments” that have been recorded in the Chinese medicinal literature for over 2,000 years. However, evidence linking interference effects with combination use is scare. Based on the estrogen-like effect of GS described in our previous studies, we undertake a characterization of the interaction on estrogenic activity of GS and VN using in vivo models of immature and ovariectomized (OVX) mice and in vitro studies with MCF-7 cells for further mechanism. VN decreased the estrogenic efficacy of GS on promoting the development of the uterus and vagina in immature mice, and reversing the atrophy of reproductive tissues in OVX mice. VN interfered with the estrogenic efficacy of GS by decreasing the increase of the serum estradiol and the up-regulation of ERα and ERβ expressions by treatment with GS. And VN antagonized the estrogenic efficacy of GS on promoting the viability of MCF-7 cells and up-regulation of protein and gene expressions of ERs. In conclusion, this study provided evidence that GS and VN decreased effects on estrogenic activity, which might be related to regulation of estrogen secretion and ERs.